2015
DOI: 10.1002/adma.201504288
|View full text |Cite
|
Sign up to set email alerts
|

Fusogenic Reactive Oxygen Species Triggered Charge‐Reversal Vector for Effective Gene Delivery

Abstract: A novel fusogenic lipidic polyplex (FLPP) vector is designed to fuse with cell membranes, mimicking viropexis, and eject the polyplex into the cytosol, where the cationic polymer is subsequently oxidized by intracellular reactive oxygen species and converts to being negatively charged, efficiently releasing the DNA. The vector delivering suicide gene achieves significantly better inhibition of tumor growth than doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
269
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(276 citation statements)
references
References 83 publications
3
269
0
1
Order By: Relevance
“…S6). Generally, it is reported that nanoparticles with smaller size and more positive surface charge can be faster internalized by cell endocytosis [49,50]. Therefore, PBI-G2.5 nanoparticles with small size and positive surface charge should have great potential in cell imaging.…”
Section: Articlesmentioning
confidence: 99%
“…S6). Generally, it is reported that nanoparticles with smaller size and more positive surface charge can be faster internalized by cell endocytosis [49,50]. Therefore, PBI-G2.5 nanoparticles with small size and positive surface charge should have great potential in cell imaging.…”
Section: Articlesmentioning
confidence: 99%
“…[172] Moreover, the transfection efficiency of the PEI carrier was compared to that of the ROS-labile charge-reversal poly((2-acryloyl)ethyl(p-boronic acid benzyl)diethylammonium bromide) (B-PDEAEA), which was recently reported by the same authors. [173] B-PDEAEA is a positively charged linear polymer that packages DNA into nanoparticles, but turns into a negatively charged polymer releasing the DNA in response to intracellular ROS. [173] It was demonstrated that the DNA was localized in the cell nucleus quickly after B-PDEAEA-mediated (13 of 26) 1700022 transfection and RO-3306 coadministration only slightly increased the transfection efficiency.…”
Section: Mitochondrial Deliverymentioning
confidence: 99%
“…[173] B-PDEAEA is a positively charged linear polymer that packages DNA into nanoparticles, but turns into a negatively charged polymer releasing the DNA in response to intracellular ROS. [173] It was demonstrated that the DNA was localized in the cell nucleus quickly after B-PDEAEA-mediated (13 of 26) 1700022 transfection and RO-3306 coadministration only slightly increased the transfection efficiency. [172] Based on these results, the authors concluded that, while most of the PEI/DNA complexes enter the nucleus in the intact form during mitosis, cytoplasmic DNA released from the negatively charged B-PDEAEA may enter the nucleus passing through the NPC.…”
Section: Mitochondrial Deliverymentioning
confidence: 99%
“…In the presence of H 2 O 2 , phenylboronic acid on MPEG 5K -P(DMAEMA-PBA) 14K was oxidized and hydrolyzed, generating MPEG 5K -P(DMAEMA) 6K with reduced positive charge (Scheme 1b), as demonstrated by 1H-NMR (Figure S3a, Supporting Information). [16] In addition, poly(DMAEMA) and poly(DMAEMA-PBA) were synthesized via ATRP initiated by ethyl α -bromoisobutyrate and subsequent quaternarization by 4-(bromomethyl)phenylboronic acid, respectively (Figures S4a,b and S5a,b, Supporting Information). Given its isoelectric point of ≈5.3, [17] insulin is negatively charged at pH 7.4 and capable of complexing with positively charged MPEG 5K -P(DMAEMA-PBA) 14K [18] to form Ins-NCs with a PEG corona and a complex core.…”
mentioning
confidence: 99%